A review on recent advancements of substructures for offshore wind turbines. (15th February 2018) - Wang, Xuefei; Zeng, Xiangwu; Li, Jiale; Yang, Xu; Wang, Haijun
Highlights: This paper reviews the substructures for offshore wind turbines. The latest development of wind energy is introduced. Different types of substructures for offshore wind turbines are demonstrated. The recent technologies for the suction bucket foundation are summarized. Challenges and future trends of the suction bucket foundation are discussed. Abstract: The sustainable development of offshore wind energy requires thorough investigations on technological issues. The substructure, which acts as the natural link between technologies and environments, is a critical topic for the offshore wind industry. This paper presents a comprehensive review of variable types of offshore wind substructures associate with their corresponding example projects. The study is complemented with a special attention to a novel foundation, namely suction bucket foundation. Main technological issues related to this concept are integrated. In the paper, bearing behaviors of offshore wind turbines (OWTs) with the suction bucket foundation under lateral loads, vertical loads, combined loads, and extreme loading conditions are discussed. Two installation methods are introduced. The geometric and improved design is illustrated by considering capabilities in transportation and installation. Research methods, including field tests, laboratory tests, centrifuge tests, theoretical analysis and numerical simulations, are listed; these methods are employed in previous studies to investigate behaviors of the OWT. This review integrates most relevant aspects and recent advancements together, which aims to provide a reference frame for future studies and projects.